2020
DOI: 10.25259/ajohas_16_2020
|View full text |Cite
|
Sign up to set email alerts
|

Awareness among health care professionals regarding interrelationship between diabetes mellitus and periodontal diseases: A step towards interprofessional collaborative practice

Abstract: Objectives: The objective of the study was to assess the level of awareness among health care professionals regarding interrelationships between diabetes mellitus (DM) and periodontal diseases. Material and Methods: A self-administered, structured questionnaire based on scientific literature, and practice was distributed among 100 non-oral health care professionals (NOHCP) and 100 oral-health care professionals (OHCP) for assessment of their awareness regarding DM and periodontitis interrelationship (DPI). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The physicians in our study were aware (90%) that PD and DM are linked, which is much higher than what is reported in the literature for physicians understanding the interrelationship between the two diseases where it is estimated to be about (50-56%). 20,[22][23][24] In a previous study, (56.7%) of the medical professionals were aware of the bidirectional relationship between systemic and periodontal diseases, while (38.6%) of them were aware of the relationship in one of either direction only. 25 The awareness of the Libyan physicians' understanding that PD can affect glycemic control was over (70%) and equivalent to what is reported in the literature for other healthcare professionals which ranges between (65-76%).…”
Section: Discussionmentioning
confidence: 96%
“…The physicians in our study were aware (90%) that PD and DM are linked, which is much higher than what is reported in the literature for physicians understanding the interrelationship between the two diseases where it is estimated to be about (50-56%). 20,[22][23][24] In a previous study, (56.7%) of the medical professionals were aware of the bidirectional relationship between systemic and periodontal diseases, while (38.6%) of them were aware of the relationship in one of either direction only. 25 The awareness of the Libyan physicians' understanding that PD can affect glycemic control was over (70%) and equivalent to what is reported in the literature for other healthcare professionals which ranges between (65-76%).…”
Section: Discussionmentioning
confidence: 96%
“…[ 93 ] However, it has often been ignored to be an imperative element of “interprofessional collaborative management approach” for T2D. [ 2 ] Therefore, oral and non-oral (medical) health professionals should line up efforts in the management of T2D-susceptible subjects with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Epidemiological studies have observed a rapidly increasing trend in DM epidemic mainly in Indian subcontinent countries. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%